2020
DOI: 10.3390/w12020317
|View full text |Cite
|
Sign up to set email alerts
|

Cover or Velocity: What Triggers Iberian Barbel (Luciobarbus Bocagei) Refuge Selection under Experimental Hydropeaking Conditions?

Abstract: The rapid river flow variations due to hydropower production during peak demand periods, known as hydropeaking, causes several ecological impacts. In this study, we assessed the potential of an overhead cover and velocity-refuge structure in an indoor flume as an indirect hydropeaking mitigation measure for the cyprinid species Iberian barbel (Luciobarbus bocagei). We designed a lab-scale LUNKERS-type structure using two different materials which were used separately: Wood (opaque) and acrylic (transparent), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 58 publications
2
25
0
Order By: Relevance
“…On the other hand, the natural-colored barrier mimics more closely natural wooden formations associated with overhead cover and shelter. A study comparing a wooden against an acrylic, transparent velocity shelter (LUNKER) showed an increase in use of the wooden structure, which was assumed to be linked to visual stimuli caused by the shade (Moreira et al, 2020). Rainbow trout possess well-developed color vision (Niwa and Tamura 1969 cited by (Nakano et al, 2012)), but we know little about their attraction to color and colored objects.…”
Section: Fish Response To Overhead Cover Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the natural-colored barrier mimics more closely natural wooden formations associated with overhead cover and shelter. A study comparing a wooden against an acrylic, transparent velocity shelter (LUNKER) showed an increase in use of the wooden structure, which was assumed to be linked to visual stimuli caused by the shade (Moreira et al, 2020). Rainbow trout possess well-developed color vision (Niwa and Tamura 1969 cited by (Nakano et al, 2012)), but we know little about their attraction to color and colored objects.…”
Section: Fish Response To Overhead Cover Experimentsmentioning
confidence: 99%
“…The piling up of these materials also increases both barrier blockage, and longitudinal barrier length, with longer barriers providing an increase in overhead cover, an essential feature in river restoration (Heggenes & Traaen, 1988). The resulting shaded area has been found to be a visual stimulus associated with refuge and enabled fish to find the covered region (Moreira et al., 2020). A wide range of leaky barrier designs can already be found worldwide but in particular in the United Kingdom where predominantly engineered leaky barriers were installed as part of 60 Department for Environment, Food, and Rural Affairs‐funded NFM projects ([Arnott et al., 2018; Burgess‐Gamble et al., 2018], e.g., Pickering, North East England; Holnicote, South West England; Peeblesshire, South Scotland; and Shropshire, West England).…”
Section: Introductionmentioning
confidence: 99%
“…At the end of each trial, to assess physiological responses to stress and fish fatigue of all tested fish, blood glucose (GLUC; mg•dL −1 ) and lactate (LACT; mmol•L −1 ) concentrations were measured using the portable meters Accucheck Aviva (Roche) and Lactate Plus (Nova Biomedical UK), respectively. The methodology applied was the same as in other studies of fish behaviour and passage performance conducted in ecohydraulic flumes [33,34,37]. The tested fish was restrained in a V-shaped padded bed, where fresh water was continuously provided, and a blood sample (0.1-0.5 mL) was collected from the caudal vasculature, using a 23 G or 25 G preheparinized needle.…”
Section: Fish Experimentsmentioning
confidence: 99%
“…In addition, along with these key physical and hydraulic parameters, physiological conditions of fish, such as stress level and fatigue, should also be considered when assessing fish passage performance [33,34]. Measurements of physiological parameters, such as glucose and lactate concentrations in blood samples, using portable point-of-care devices [35], are frequently applied to assess exercise effort and fish physiological responses to stress [33][34][35][36][37]. However, most studies are mainly focused on salmonids, as well as other game fish species such as largemouth bass or pike [35,38,39], and less is known about physiological responses for potamodromous cyprinids.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still a lack of studies conducted with cyprinids and in an ‘in situ’ context. Most of the existent or recent studies were carried out as experiments through flumes in an ‘ex situ’ context (e.g., Costa, Boavida, Almeida, Cooke, & Pinheiro, 2018; Costa, Fuentes‐Pérez, et al, 2019; Costa, Pinheiro, et al, 2019; Moreira, Costa, Valbuena‐Castro, Pinheiro, & Boavida, 2020), which hardly represent all the habitat conditions and the complexity of factors inherent to the natural environment where fish inhabit.…”
Section: Introductionmentioning
confidence: 99%